The Guidelines for the Administration of Student Support System in Student Affairs of Nonthaburi Vocational Education Office - Koingoen, Veerapol; Namawiroj, Panot (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were 1) to study the guideline for administration of student support system in student affairs, 2) to compare on guideline for administration of student support system in student affairs classified by position, education level, work experience and school size, and 3) to study the guideline for administration of student support system in student affairs of Nonthaburi Vocational Education Office. The sample consisted of 5 expert and 248 school administrator and teachers. The research instrument was a interview and questionnaire with content validity, IOC values 1.00 all items and a reliability value of .96. The data were analyzed by using frequency, percentage, mean, standard deviation, t-test, One-way ANOVA, LSD and content analysis. The results of the research were as follows: 1) the administration of student support system in student affairs of Nonthaburi Vocational Education Office was a high level in over all and particular aspects 2) the administration of student support system in student affairs of Nonthaburi Vocational Education Office classified by position and school size were not difference, while classified by education level and work experience were statistically significant at the level of .01 and .05 3) Guidelines for administration of student support system in student affairs of Nonthaburi Vocational Education Office, School administrators should focus on the importance of understanding students individually, collecting in-depth information about students to group them, organizing various activities, emphasizing prevention and problem solving, especially for at-risk groups, and referring cases that cannot be cured.